TINGKAT LITERASI WAQF DAN DETERMINANNYA TERHADAP NIAT MASYARAKAT BERKONTRIBUSI WAQF TUNAI: STUDI LEMBAGA WAQF DI INDONESIA - Rahmania, Nurul; Maulana, Hartomi (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This study aims to analyze the literacy level of public interest in paying cash waqf at waqf institutions in Indonesia. The theory of planned behavior (TPB) was used as the research framework. Structural equation modeling (SEM) to measure the relationship between latent variables, namely religious compliance, involvement of waqf organizations, utilization of media technology tools, elements of education, attitudes, subjective norms, and behavioral control employed as the main analysis technique. The SEM model in this study was processed using SmartPLS 3.0. The results showed that subjective norms and religious observance had a significant effect on interest, elements of education and the utilization of media technology tools had a significant effect on PBC, and the involvement of waqf organizations had a significant effect on attitudes. PBC has a significant negative effect on interest, religious compliance has a significant negative effect on attitudes. Meanwhile, attitude has no significant effect on interest.